Molecular Identification And Conservation Status Of Sharks From The Fins Trade In Manado City North Sulawesi - Mopay, Maratade; Wullur, Stenly -; Onibala, Hens -; Ginting, Elvy Like; Rumengan, Inneke F. M; Sondak, Calvyn F.A; Sumilat, Deiske A. (Sam Ratulangi University, 2021)
Sharks are a group of cartilaginous fish that are vulnerable to overfishing. Genetics approaches play an important role in shark conservation. Shark fishing has become the main activity of fishermen in several areas, including in North Sulawesi. This research is focused on the molecular aspects and conservation status of shark species obtained from the shark fin trade in Manado, North Sulawesi. COI gene was amplified using Fish BCL5 (for) and HCO219 (rev) primers. Nucleotide sequences of each sample were aligned with the closest sequences in the GenBank database using the BLAST (Basic Local Alignment and Search Tool) method. The conservation status of the shark species is carried through the IUCN (International Union for the conservation of nature red list) Red list website. Molecular identification results showed that the shark’s fins from Manado had high similarity with Carcharhinus falciformis (HM1 and HM2) and Carcharhinus melanopterus (HM3). According to IUCN red list data, the C. falciformis and C. melanopterus were categorized as vulnerable to extinction (VU).Keywords: Molekuler; COI; Shark; Manado and IUCN Red list . AbstrakHiu merupakan kelompok ikan bertulang rawan yang sangat rentan terhadap dampak penangkapan secara berlebihan. Informasi terkait genetik hiu yang semakin terancam populasinya sangat berperan penting dalam upaya konservasi hiu. Penangkapan hiu telah menjadi aktivitas utama nelayan di beberapa daerah, termasuk di Sulawesi Utara. Penelitian ini difokuskan pada aspek molekuler dan penentuan status konservasi spesies hiu menggunakan sampel sirip yang di dapatkan dari perdagangan sirip hiu, di kota Manado. Amplifikasi gen COI dilakukan dengan menggunakan primer Fish BCL5 (for) dan HCO219 (rev). Sekuens nukleotida masing-masing sampel disejajarkan dengan nukleotida terdekat yang ada dalam database genbank menggunakan metode BLAST (Basic Local Aligment and Search Tool) Penentuan status konservasi dilakukan melalui penelusuran spesies rujukan di situs IUCN (International Union for the Conservation of Nature) Red list. Hasil identifikasi molekuler menunjukan bahwa sampel sirip hiu dari kota Manado memiliki kemiripan yang tinggi dengan spesies : Carcharhinus falciformis (HM1 dan HM2) dan C. melanopterus (HM3). Menurut data IUCN Red list, C. falciformis dan C. Melanopterus merupakan jenis hiu dalam status konservasi rentan punah (VU). Kata Kunci: Molekuler; COI; hiu; Manado dan IUCN Red list